PENGARUH DUKUNGAN KELUARGA TERHADAP SIKAP KEPALA KELUARGA TENTANG PENYAKIT FILARIASIS DI RW 02 KAMPUNG DUSUN PUSAKA KECAMATAN PUSAKO KABUPATEN SIAK - Rifa Yanti; Fitra Mayenti (STIKes Payung Negeri Pekanbaru, 2018)
Background : Filariasis is one of the most commonly recognized diseases in the world of health, more than 1 billion of the world's population at risk of filariasis and more than 120 million people from 80 countries had been infected with filariasis. WHO (World Health Organization) had launched a global agreement to eradicate filariasis with The Global Goal of Elimination of Lymphatic Filariasis by Health Health Problem by the Year 2020 (WHO, 2010). In 2003, filariasis disease in Indonesia was reported as many as 6,571 cases. In 2007 there were 11,473 cases and in 2008 there were 11,699 cases then increased to 11,914 cases in 2009. Nearly thousands of villages in 26 provinces in Indonesia were declared endemic (Health Ministry of Indonesia, 2010). The purpose of this study was to know the effect of family support with the attitude of the head of the family about filariasis disease in RW 02 Kampung Dusun Pusaka Kecamatan Pusako Siak District. Quantitative observational research method with cross sectional approach. Data collection was done by distributing questionnaires and analyzed univariat and bivariate. Results of the study were 116 respondents, 62.1% good family support and 37.9% poor family support, and attitude of family head 60,3% positive and 39,7% respondent attitude negatiif. The result of statistical test showed that there was significant influence between family support and family head attitude about filariasis disease (p.Value = 0,00). it is expected to the health officer to be more actively activate and give counseling about filariasis disease specially in RW 02.